Analisis Manajemen Risiko Pada UMKM Pengolahan Produk Eco Enzyme - Dea Kuni Fauziyah; Salsabila Fauziah; Asep Suwarna (Indo Publishing, 2026)
This study aims to analyze the implementation of risk management in a home-based micro, small, and medium enterprise (MSME) producing Eco Enzyme products in Bandung. A qualitative descriptive approach was employed, with data collected through in-depth interviews and direct observation of production, packaging, and marketing activities. The results indicate that the MSME faces several types of risks, including production, operational, financial, marketing, and environmental as well as customer trust risks. The most significant risks identified are variations in product quality due to raw material characteristics, limited production capacity caused by single-person management, and price sensitivity in the market. Despite these challenges, the business owner has implemented simple yet effective risk management strategies through hands-on supervision, experience-based production control, secure packaging, manual financial records, and environmentally focused digital marketing. The consistent application of risk management practices supports business sustainability, maintains product quality, and strengthens customer trust. This study highlights the importance of risk management as a key factor in enhancing the resilience and long-term sustainability of environmentally friendly MSMEs.